(untitled) (Chicago, IL, 2012)
Offering multiple perspectives from electronic resource professionals at world-renowned libraries such as Harvard, the University of Michigan, Duke, and Northeastern, this book provides a comprehensive and well-rounded e-book education. Success stories highlight each chapterOCOs lessons, giving you real-world examples of effective e-book implementation in both school and public libraries
Keywords: Libraries,Thư viện; Special collections,Electronic books,Bộ sưu tập đặc biệt,Sách điện tử